A Study on Evaluation of Some Herbal Medicinal Products Microbial Qualities: Ensuring Quality and Safety in the Global Herbal Market (Journal of Advances and Scholarly Researches in Allied Education, 2022)
In today's modern medical practise, there is a growing understanding and universal acceptanceof the utilisation of herbal medications. It is a well-known truth that more than 80 percent of the world'spopulation relies on herbal medications and products for healthy living, despite the fact that the majorityof these applications are unconventional. There has been a rise in the overuse and adulteration of herbalproducts as a result of this popularity. This has resulted in frustration on the part of consumers andmanufacturers alike, and in extreme circumstances, even death. Because of the immensity and breadthof the problem, the international market for herbal products is now unreliable. The purpose of this reviewis to inform those with an interest in herbal medicine of the need to create quality guidelines for thecollection, handling, processing, and manufacture of herbal medicine and to use these parameters in theprocess of maintaining the safety of the global herbal market. These objectives will be accomplished byshedding light on these matters through this review. The methods of assuring herbal medications andproducts are of a high grade and complying with industry standards were also highlighted.